A growth model for the quadruple helix - Afonso, Oscar; Monteiro, Sara; Thompson, Maria (Journal of Business Economics and Management, 2012)
We develop a R&D-based growth model with productive public expenditure in order to frame the Quadruple Helix (QH) innovation concept, based on four helices: Academia & Technological Infrastructures, Firms, Government and Civil Society. Our motivation stems from acknowledgment that the relationship between these four helices and their joint impact on growth is in need of a theoretical framework. We aim to emphasise the importance to economic growth of innovation systems structured on these four helices. The introduced model confirms theoretically the notion that increases in: (i) complementarities between distinct productive units, or (ii) in productive government expenditure, lead to higher growth.